Treatment of posttraumatic stress disorder : an assessment of the evidence (National Academies Press, 2008)
"Prior to the military conflicts in Iraq and Afghanistan, wars and conflicts have been characterized by such injuries as infectious diseases and catastrophic gunshot wounds. However, the signature injuries sustained by United States military personnel in these most recent conflicts are blast wounds and the psychiatric consequences to combat, particularly posttraumatic stress disorder (PTSD), which affects an estimated 13 to 20 percent of U.S. service members who have fought in Iraq or Afghanistan since 2001. PTSD is triggered by a specific traumatic event - including combat - which leads to symptoms such as persistent re-experiencing of the event; emotional numbing or avoidance of thoughts, feelings, conversations, or places associated with the trauma; and hyperarousal, such as exaggerated startle responses or difficulty concentrating. As the U.S. reduces its military involvement in the Middle East, the Departments of Defense (DoD) and Veterans Affairs (VA) anticipate that increasing numbers of returning veterans will need PTSD services. As a result, Congress asked the DoD, in consultation with the VA, to sponsor an IOM study to assess both departments' PTSD treatment programs and services. Treatment for Posttraumatic Stress Disorder in Military and Veteran Populations: Initial Assessment is the first of two mandated reports examines some of the available programs to prevent, diagnose, treat, and rehabilitate those who have PTSD and encourages further research that can help to improve PTSD care."--